2003
DOI: 10.1046/j.1365-2958.2003.03525.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Pseudomonas aeruginosa wild type, flagella and type IV pili mutants

Abstract: SummaryBiofilm formation by Gfp-tagged Pseudomonas aeruginosa PAO1 wild type, flagella and type IV pili mutants in flow chambers irrigated with citrate minimal medium was characterized by the use of confocal laser scanning microscopy and COMSTAT image analysis. Flagella and type IV pili were not necessary for P. aeruginosa initial attachment or biofilm formation, but the cell appendages had roles in biofilm development, as wild type, flagella and type IV pili mutants formed biofilms with different structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
779
4
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 899 publications
(855 citation statements)
references
References 49 publications
35
779
4
20
Order By: Relevance
“…This confirmed that transcription of the pilMNOPQ operon was decreased in the mutant throughout all phases of growth. Depending on the carbon source used, type IV pili are not always necessary for the initial attachment of P. aeruginosa PAO1, but they are always necessary for normal biofilm development, irrespective of growth medium (Klausen et al, 2003). Under the conditions used for this transcriptome study (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed that transcription of the pilMNOPQ operon was decreased in the mutant throughout all phases of growth. Depending on the carbon source used, type IV pili are not always necessary for the initial attachment of P. aeruginosa PAO1, but they are always necessary for normal biofilm development, irrespective of growth medium (Klausen et al, 2003). Under the conditions used for this transcriptome study (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains and culture conditions P. aeruginosa strains American Type Culture Collection (ATCC) 27853; National Collection of Type Cultures (NCTC) 10662, SG137, and PAO1; and the PAO1 derivative AH377 (24) were routinely cultured in enriched nutrient broth (NB; Serva, Amstetten, Austria) at 37˚C. Thirteen clinical isolates were derived from patients with different diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Resistance to phages due to modified type IV pili has consequences for bacterial motility by affecting twitching -a form of solid surface translocation (Chiang & Burrows, 2003). Type IV pili allow the adherence of P. aeruginosa cells to the host epithelium and also play a role in biofilm formation (Bucior et al, 2012;Klausen et al, 2003;O'Toole & Kolter, 1998). The mechanism of resistance associated with the loss of pili may drive an increase in P. aeruginosa diversity and strongly reduce infectivity…”
Section: Introductionmentioning
confidence: 99%